Cis-acting regions sufficient for spermatocyte-specific transcriptional and spermatid-specific translational control of the Drosophila melanogaster gene mst(3)gl-9. - Kuhn, R (1988)
In Drosophila spermatogenesis transcription occurs only premeiotically while translation can be detected also in postmeiotic spermatids. To analyse the underlying processes mst(3)gl-9, a gene specifically expressed in the male germ cells of Drosophila melanogaster, was studied. The putative protein encoded by mst(3)gl-9 is mostly composed of repetitive Cys-Gly-Pro motifs. The transcriptional and translational control of expression of mst(3)gl-9 has been investigated by P-mediated transformation. Only 102 bp of 5' upstream sequences and the first 201 bp of the gene are sufficient to maintain the gene specific characteristics of expression, namely premeiotic transcription and postmeiotic translation separated by 3 days of development.